2007
DOI: 10.1634/stemcells.2007-0621
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Putative Gastrointestinal Stem Cell and Adenoma Stem Cell Marker, Doublecortin and CaM Kinase-Like-1, Following Radiation Injury and in Adenomatous Polyposis Coli/Multiple Intestinal Neoplasia Mice

Abstract: In the gut, tumorigenesis arises from intestinal or colonic crypt stem cells. Currently, no definitive markers exist that reliably identify gut stem cells. Here, we used the putative stem cell marker doublecortin and CaM kinase-like-1 (DCAMKL-1) to examine radiation-induced stem cell apoptosis and adenomatous polyposis coli (APC)/multiple intestinal neoplasia (min) mice to determine the effects of APC mutation on DCAMKL-1 expression. Immunoreactive DCAMKL-1 staining was demonstrated in the intestinal stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
267
2
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(292 citation statements)
references
References 27 publications
20
267
2
3
Order By: Relevance
“…In the mouse small intestine, Msi-1 and Hes-1 are co-expressed in the cells just above the Paneth cell zone, although Hes-1 expression additionally extends to proliferative cells higher up the crypt [102]. Msi-1 also co-localizes with another putative stem cell marker, DCAMKL-1, at cell position 4 [103]. Potten et al [67] observed Msi-1 expression, not only at cell positions 4-5, where LRCs exist, but also in crypt base columnar cells (CBCs, Figure 6E).…”
Section: Digestive Tractmentioning
confidence: 99%
“…In the mouse small intestine, Msi-1 and Hes-1 are co-expressed in the cells just above the Paneth cell zone, although Hes-1 expression additionally extends to proliferative cells higher up the crypt [102]. Msi-1 also co-localizes with another putative stem cell marker, DCAMKL-1, at cell position 4 [103]. Potten et al [67] observed Msi-1 expression, not only at cell positions 4-5, where LRCs exist, but also in crypt base columnar cells (CBCs, Figure 6E).…”
Section: Digestive Tractmentioning
confidence: 99%
“…Two subpopulations of stem cells have recently been identified in the intestinal epithelium (1)(2)(3). It has been shown that loss of Apc in one of these stem cell subpopulations results in intestinal adenomas (4).…”
mentioning
confidence: 99%
“…As expected, the majority of the mouse colonic epithelium AR cells were positive for the stem or progenitor cell marker CD133. Further characterization revealed that mouse colonic AR cells express DCLK1 and Hopx, which have been reported as a +4 position cell marker [16,29], but negative for Lgr5, Msi1 and Bmi1.…”
Section: Discussionmentioning
confidence: 87%
“…It also mediates fiber tract decussation and neuronal migration during brain development [13]. Although DCLK1 has been considered to be a marker of putative quiescent stem cells [9,16,17], recent findings have revealed that it marks a subset of colorectal stem cells, and also a rare subset of epithelial cells called tuft cells [7,8]. In the present experiment, an immunohistochemical investigation of the mouse colon revealed that DCLK1/ CD133 double positive cells are located not only in basal crypt, but also in apical crypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation